2018
DOI: 10.1002/tal.1570
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tests for improving buildability of construction methods for high‐strength concrete columns in high‐rise buildings

Abstract: High-strength concrete columns have the advantage of increasing the amount of usable area in the building because the cross-section of the columns takes up less space compared with columns using normal strength concrete. However, it is difficult to weld the steel reinforcement and steel members because of the narrow column width due to a decrease in the cross-section of the column, thereby causing construction delay in many cases. In this paper, five construction methods with different details for high-strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The study of buildability in construction has been the interest of several researchers (Osuizugbo, 2020b; Shim et al , 2019; Li et al , 2018; Jarkas, 2016; Singhaputtangkul and Low, 2015; Lam et al , 2012; Jarkas, 2012a, 2012b, 2012c; Nourbakhsh et al , 2012; Mydin et al , 2011; Jarkas, 2010a; Jarkas, 2010b; Lam and Wong, 2009; Nielsen et al , 2009; Lam and Wong, 2008; Lam et al , 2007; Wong et al , 2006a, 2006b; Mbamali et al , 2005; Low, 2001; Hyde, 1995; Hildon and Howrie, 1987) to mention a few. However, a careful examination of the literature revealed a dearth of research into the factors supporting the implementation of buildability assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The study of buildability in construction has been the interest of several researchers (Osuizugbo, 2020b; Shim et al , 2019; Li et al , 2018; Jarkas, 2016; Singhaputtangkul and Low, 2015; Lam et al , 2012; Jarkas, 2012a, 2012b, 2012c; Nourbakhsh et al , 2012; Mydin et al , 2011; Jarkas, 2010a; Jarkas, 2010b; Lam and Wong, 2009; Nielsen et al , 2009; Lam and Wong, 2008; Lam et al , 2007; Wong et al , 2006a, 2006b; Mbamali et al , 2005; Low, 2001; Hyde, 1995; Hildon and Howrie, 1987) to mention a few. However, a careful examination of the literature revealed a dearth of research into the factors supporting the implementation of buildability assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature on buildability is extensive (Osuizugbo et al. , 2022a, b, c; Samarasinghe and Piri, 2021; Osuizugbo, 2020a; Shim et al. , 2019; Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Buildability is a key necessity for improving the designs of construction projects. The existing literature on buildability is extensive (Osuizugbo et al, 2022a, b, c;Samarasinghe and Piri, 2021;Osuizugbo, 2020a;Shim et al, 2019;Li et al, 2018;Jarkas, 2010aJarkas, , 2012aJarkas, , b, 2016Singhaputtangkul and Low, 2015;Lam et al, 2007Lam et al, , 2012Nourbakhsh et al, 2012;Mydin et al, 2011;Singhaputtangkul et al, 2011;Wong, 2008, 2009;Nielsen et al, 2009;Low et al, 2008;Wong et al, 2006b, Mbamali et al, 2005Low, 2001) and it has focused particularly on developed countries. In recent time for example, the studies by Samarasinghe and Piri (2021) found out that virtual reality models have significant benefits for assessing design buildability in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34 ] Using high‐strength concrete improves the structural performance, reduces the cross‐sectional size at the same condition, and increases the rigidity of structural members, thereby reducing the deformation. [ 35 ] However, the research on the application of high‐strength recycled concrete is also limited. This study aimed to expand the application of high‐strength recycled concrete and investigate the effect of recycled aggregates on the seismic performance of high‐strength concrete columns under high ACRs for similar concrete strengths.…”
Section: Introductionmentioning
confidence: 99%